Registration of 'Ray' Hard Red Winter Wheat. Issue 3 (1st September 2019) - Bruckner, P. L.; Berg, J. E.; Lamb, P. F.; Carr, P.; Wichman, D. M.; Miller, J. H.; Meccage, E.; Miller, Z.; Chen, C.; Kephart, K. D.; Eberly, J. O.; Pradhan, G. P.; et al.
Abstract : 'Ray' (Reg. no. CV‐1156, PI 689754) hard red winter wheat ( Triticum aestivum L.) was developed and released by the Montana Agricultural Experiment Station in 2018. Ray was derived from the backcross population, 'Yellowstone'*2/98X168‐1. The line 98X168‐1 is an unreleased Montana forage breeding line. Ray was developed using the pedigree breeding method and selected as an F4:5 headrow. It was tested under the experimental number MTF1432 in Montana grain and forage yield trials from 2014 to 2018. Ray is suitable in Montana as a dual‐purpose forage and grain cultivar with dry matter forage yield and quality in a one‐cut annual hay harvest evaluation similar to 'Willow Creek' winter wheat, and grain production and end‐use quality characteristics similar to the widely grown, high‐yielding Montana hard red winter wheat grain cultivar Yellowstone.